ANALISIS BIBLIOMETRIK TREN PEMBELAJARAN BERBASIS GAME DALAM MENINGKATKAN HASIL BELAJAR MATEMATIKA SISWA - Cantika, Fadiya Puteri; Rinaldi, Achi; Dewi, Novian Riskiana (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study presents a bibliometric analysis of game-based learning to improve students’ mathematics achievement using Google Scholar data. A total of 29 relevant articles were analyzed with Publish or Perish and VOSviewer. The results show a rising trend in publications from 2021 to 2024, reflecting growing interest in the topic. Keyword mapping generated 12 clusters with dominant terms like “game-based learning” and “learning outcomes.” Emerging terms such as “critical thinking” and “interactive media” suggest future research potential. Wordwall and Quizizz were the most frequently cited platforms. This study provides an overview of current trends and future research opportunities.